96. Buried side by side: The last hunter-gatherers of the south-western Iberian Peninsula through the lens of their mortuary practices - Stjerna, Rita Peyroteo (2021)
This paper summarizes the results of my research (Peyroteo-Stjerna 2016a) focusing on burial activities of the last hunter-gatherers of the south-western Iberian Peninsula. Human burials were investigated in terms of time and practice based on the application of three methods: radiocarbon dating and Bayesian analysis to define the chronological framework of the burial activity at each site and valley; stable isotope analysis of carbon and nitrogen aimed at defining the burial populations by the identification of dietary choices; and archaeothanatology to reconstruct and define central practices in the treatment of the dead. This research provides new perspectives on the role and relevance of the shell middens in the Tagus and Sado Valleys. Death rituals played a central role in the life of these hunter-gatherers in developing a sense of community, as well as for maintaining social ties in both life and death.